The metal distribution and the change of physiological and biochemical process in soybean and mung bean plants under heavy metal stress. Issue 11 (19th September 2018) - Mao, Fei; Nan, Guanjun; Cao, Meng; Gao, Yuqiong; Guo, Liying; Meng, Xianxin; Yang, Guangde
ABSTRACT: Soybean [ Glycine max (Linn.) Merrill] and mung bean [ Vigna radiate (Linn.) Wilczek] plants were challenged with 5 kinds of heavy metals [cadmium (Cd), chromium (Cr), copper (Cu), lead (Pb) and mercury (Hg)] in a hydroponic system. We applied 4 different metal treatments to study the effects of heavy metals on several physiological and biochemical parameters in these species, including root length, heavy metal concentrations and allocation in different organs, superoxide dismutase, catalase, and peroxidase activities, the content of malondialdehyde (MDA), protein and chlorophyll. The data showed that the growth of the roots of soybean and mung bean was equally sensitive to external Hg concentrations. Soybean was more sensitive to external Cd concentrations, and mung bean was more sensitive to external Cr, Cu and Pb concentrations. Normal concentrations of heavy metal would not cause visible toxic symptoms, and a low level of heavy metal even slightly stimulated the growth of plants. With the rise of heavy metal concentration, heavy metal stress induces an oxidative stress response in soybean and mung bean plants, characterized by an accumulation of MDA and the alternation pattern of antioxidative enzymes. Meanwhile, the growth of plants was suppressed, the content of chlorophyll decreased and leaves showed chlorosis symptoms at high metal concentrations.